Joint venture sebagai Mekanisme Strategis Masuknya Investasi Asing Langsung di Negara Berkembang - Nur Anita Chandra Putry; Umi Wahidah; Nurul Fitratun; Muchammad Sajid; Maria Ulrike Lorwina Settu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the role of joint ventures as a strategic entry mode for foreign direct investment (FDI) in developing countries characterized by economic, political, and institutional uncertainties. Using a descriptive qualitative approach, the findings reveal that joint ventures are chosen because they reduce risk while providing foreign investors with market access, legitimacy, and valuable local knowledge through collaboration with domestic partners. The results indicate that joint ventures function not only as a means of sharing resources and adapting to local conditions but also as a mechanism that benefits host countries through technology transfer, enhanced industrial capabilities, and strengthened economic competitiveness. Thus, joint ventures emerge as a mutually beneficial strategy for both multinational investors and developing economies.